DNA methylation profiling of CD04+/CD08+ T cells reveals pathogenic mechanisms in increasing hyperglycemia: PIRAMIDE pilot study. (December 2020) - Benincasa, Giuditta; Franzese, Monica; Schiano, Concetta; Marfella, Raffaele; Miceli, Marco; Infante, Teresa; Sardu, Celestino; Zanfardino, Mario; Affinito, Ornella; Mansueto, Gelsomina; Sommese, Linda; Nicoletti, Giovanni Francesco; et al.
Abstract: Background: DNA methylation can play a pathogenic role in the early stages of hyperglycemia linking homeostasis imbalance and vascular damage. Material and methods: We investigated DNA methylome by RRBS in CD04 + and CD08 + T cells from healthy subjects (HS) to pre-diabetics (Pre-Diab) and type 2 diabetic (T2D) patients to identify early biomarkers of glucose impairment and vascular damage. Our cross-sectional study enrolled 14 individuals from HS state to increasing hyperglycemia (pilot study, PIRAMIDE trial, NCT03792607). Results: Globally, differentially methylated regions (DMRs) were mostly annotated to promoter regions. Hypermethylated DMRs were greater than hypomethylated in CD04 + T cells whereas CD08 + T showed an opposite trend. Moreover, DMRs overlapping between Pre-Diab and T2D patients were mostly hypermethylated in both T cells. Interestingly, SPARC was the most hypomethylated gene in Pre-Diab and its methylation level gradually decreased in T2D patients. Besides, SPARC showed a significant positive correlation with DBP (+0.76), HDL (+0.54), Creatinine (+0.83), LVDd (+0.98), LVSD (+0.98), LAD (+0.98), LVPWd (+0.84), AODd (+0.81), HR (+0.72), Triglycerides (+0.83), LAD (+0.69) and AODd (+0.52) whereas a negative correlation with Cholesterol (−0.52) and LDL (−0.71) in T2D. Conclusion: SPARC hypomethylation in CD08 + T cells may be a useful biomarker of vascular complications in Pre-Diab with a possible role for primary prevention warranting further multicenter clinical trials to validate our findings. Highlights: We conducted the first methylome analysis by RRBS platform in circulating CD04 + and CD08 + T cells in increasing hyperglycemia. This approach has revealed possible biomarkers for cardiovascular and kidney complications in prediabetes. SPARC hypomethylation may underly a pro-fibrotic endophenotype to be validated in larger multicenter trials.